Program Inovasi “Dekating Nule” (Gerakan Pemberdayaan, Kader Peduli Stunting dengan kreasi Nugget Lele) untuk meningkatkan pengetahuan Kader Sebagai Upaya Pencegahan Stunting - Purba, Santi Widya; Maimunah, Siti; Rusliani, Dian Monalisa; Santi Widya Purba, Santi Widya Purba (LPPM STIKES Guna Bangsa Yogyakarta, 2025)
This community service activity, titled “Dekating Nule Innovation Program” (Empowerment Movement of Stunting-Aware Cadres through Catfish Nugget Creation), was aimed at 20 posyandu (integrated health service post) cadres. The program aimed to enhance the knowledge of health cadres in Sudirejo II Subdistrict regarding the nutritional content of catfish, which is highly beneficial in preventing stunting. The activity also introduced a practical method of processing catfish—an affordable and nutritious source of protein-into nuggets, a food form that is generally well-liked by children. Following the implementation of this program, participants were expected to have an improved understanding of catfish nutrition and how to prepare it into child-friendly meals. They would then be able to disseminate this information to mothers in Sudirejo II who have young children, thereby raising awareness of the benefits of catfish consumption. Ultimately, this knowledge enhancement among cadres is intended to contribute to reducing stunting cases among children in the area.